(untitled) (Laisvalaikio tyrimai, 2020)
Research background. Today, in order for the company to be easily recognized and stay in the trend, there is not enough ordinary advertising. It should be a progressive design work. Advertising is an important element in the development of a market economy, it should carry the continuation of the dynamic corporate identity. Motion design in advertising provides identification. Effectively using the visual memory of consumers and using stable forms of "one among strangers", creates a positive emotional attitude. Also, the use of motion elements in advertising emphasizes the company’s trend. Research goal – systematization of approaches regarding the definition of the concept of motion design. Research objectives: to reveal the role and main characteristics of motion design in the formation of a dynamic corporate identity of a company; to explore the main aspects of motion design in the formation of a dynamic corporate identity of the company. Methods. Abstracting, comparative analysis and synthesis, systematic and structured dynamic styles of Ukrainian and international companies, which made it possible to highlight the significant role of motion design in increasing brand awareness of the company. Results. The role of motion design in the formation of a dynamic corporate identity is revealed, the basic requirements are identified, and the trends in the advertising of enterprises realized with the help of motion design in the continuation of a dynamic corporate identity are analyzed. Conclusions. The development of companies translates into a qualitative change in the life realities of a person in the context of globalization and a dynamic change of news. Among the huge flow of information, advertising is a necessary tool for influencing the consumer to consolidate the dynamic image of the company. Well-designed motion design allows you to combine different groups of products under a single brand, which enhances the advertising impact on the consumer. Keywords: motion design, promotion, brand, color, dynamic corporate identity